The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1046/j.1432-1327.1998.2540209.x
|View full text |Cite
|
Sign up to set email alerts
|

Clamping down on clamps and clamp loaders

Abstract: DNA transactions such as DNA replication and DNA repair require the concerted action of many enzymes, together with other proteins and non-protein cofactors. Among them three main accessory proteins, replication factor C (RF-C), proliferating-cell nuclear antigen (PCNA) and replication protein A (RP-A), are essential for accurate and processive DNA synthesis by DNA polymerases. RF-C is a complex consisting of five polypeptides with distinct functions. RF-C can bind to a template-primer junction and, in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 9 publications
(14 reference statements)
1
124
0
Order By: Relevance
“…40,50 Interestingly, these proteins were found accumulated in the nuclear matrix fraction not only during apoptosis, but also in normal HeLa cells during G1/S transition (C Gerner and W Mikulits, unpublished data). This observation may suggest the induction of replicative foci and of DNA repair during apoptosis as described by others.…”
Section: Dna Replication and Repair During Apoptosismentioning
confidence: 99%
“…40,50 Interestingly, these proteins were found accumulated in the nuclear matrix fraction not only during apoptosis, but also in normal HeLa cells during G1/S transition (C Gerner and W Mikulits, unpublished data). This observation may suggest the induction of replicative foci and of DNA repair during apoptosis as described by others.…”
Section: Dna Replication and Repair During Apoptosismentioning
confidence: 99%
“…RFC loads the "sliding clamp" PCNA (proliferating cell nuclear antigen) onto DNA during replication. The loading of PCNA onto DNA by RFC is an important step in DNA replication and increases the processivity of DNA polymerase [32]. The RFC subunits share eight regions of high sequence similarity that include regions involved in protein complex formation, DNA binding, PCNA binding and DNA replication [32].…”
Section: Pfrfc-5 and Pfmcm6 Interact With Pfmrk In The Bacterial Two-mentioning
confidence: 99%
“…The loading of PCNA onto DNA by RFC is an important step in DNA replication and increases the processivity of DNA polymerase [32]. The RFC subunits share eight regions of high sequence similarity that include regions involved in protein complex formation, DNA binding, PCNA binding and DNA replication [32]. The motifs identified in PfRFC-5 when queried on the NCBI Entrez website (http://www.ncbi.nlm.nih.gov/Structure/cdd/cddsrv.cgi) include (i) an ATP-binding site encompassing residues 41-48 and residues 132 and 161, (ii) the WalkerA motif {consensus sequence GxxGxGK(S/T)} encompassing residues 40-47, (iii) the WalkerB motif consensus {contains four aliphatic residues followed by two negatively-charged residues}, encompassing residues 128-133 and (iv) an Arginine finger, residue 175 (Fig.…”
Section: Pfrfc-5 and Pfmcm6 Interact With Pfmrk In The Bacterial Two-mentioning
confidence: 99%
“…Evidence has accumulated that MyD/Gadd proteins display a complex array of physical interactions, including homologous and heterologous interactions with each other, as well as with products of cell cycle regulatory genes. It was found that MyD118 and Gadd45 associate with PCNA Hall et al, 1995;Vairapandi et al, 1996), which plays a central role in DNA repair and DNA replication (Mossi and Hubscher 1998;Prosperi, 1997;Jonsson and Hubscher, 1997). MyD118 and Gadd45 were shown also to associate with the cyclin dependent kinase inhibitor p21 (Vairapandi et al, 1996), known to interact with PCNA and to inhibit DNA replication Li et al, 1994;Flores-Rozas et al, 1994).…”
Section: Myd116 ± Viral Homologs and A Protective Role In Apoptosismentioning
confidence: 99%